2019
DOI: 10.1186/s13104-019-4543-2
|View full text |Cite
|
Sign up to set email alerts
|

Research, recruitment and observational data collection in care homes: lessons from the PACE study

Abstract: Objective Care homes are a common place of death for older adults, especially those with complex health needs or dementia. Representative, internationally comparable data on care home facilities and their residents is needed to monitor health and wellbeing in this population. Identification and collection of data from care homes can be challenging and often underreported. This paper draws on the experiences of the PACE study, a cross sectional mortality follow back study conducted in six European … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 15 publications
1
21
0
Order By: Relevance
“…The data used in this analysis are from a cross-sectional, mortality follow back survey of deceased residents; the PACE study [35]. The PACE study was conducted in a sample created, where possible, using national lists of LTCFs in Belgium, England, Finland, Italy, the Netherlands and Poland, recruited using a proportionally stratified random sampling framework [36].…”
Section: Study Design and Settingmentioning
confidence: 99%
“…The data used in this analysis are from a cross-sectional, mortality follow back survey of deceased residents; the PACE study [35]. The PACE study was conducted in a sample created, where possible, using national lists of LTCFs in Belgium, England, Finland, Italy, the Netherlands and Poland, recruited using a proportionally stratified random sampling framework [36].…”
Section: Study Design and Settingmentioning
confidence: 99%
“…These challenges are also present in countries with similar aged care systems to Australia. The Palliative Care for Older People in care and nursing homes in Europe (PACE) research program was conducted across six countries, which included the UK, the Netherlands, Belgium, Finland, Poland and Italy 7 . The study reported additional challenges with recruiting and conducting research in the UK compared to the other countries.…”
Section: Introductionmentioning
confidence: 99%
“…To date, research in care homes has enhanced understanding in multiple areas including end of life care (Amador et al , 2014; Goodman et al , 2015; Collingridge Moore et al , 2019), care home cultures (DeForge et al , 2011; Killett et al , 2016; McCormack et al , 2012), use of monitoring technologies (Hall et al , 2017) and residents’ experiences of mealtimes (Watkins et al , 2017). However, a review of care home research concluded that the research base for improvements in the lives of care-home residents remains underdeveloped (NIHR, 2017).…”
mentioning
confidence: 99%
“…Overall, there is a need for reflexivity in care home research (Luff et al , 2015; Collingridge Moore et al , 2019). Hall et al (2009) advocate patience and extra time to overcome challenges in gaining consent from residents and ensuring privacy during interviews within care-home settings.…”
mentioning
confidence: 99%